INTRA-SYSTEM SHIFT ANALYSIS IN THE TRANSLATION OF TOURISM BROCHURE - Putu Diah Kumala Putri (LPPM Universitas Dhyana Pura, 2023)
This study aims to analyze the shift in translation from translation studies on thetranslation shift one on the Prambanan Temple Brochure in translation by Catford(1965). From Bahasa Indonesia as Source English (SL) English target language (TL).This research is a qualitative research method. Intra-system shift was collected bynon-participation and using note-taking techniques to collect relevant data from thePrambanan Temple Tourism Brochure. The analysis used in this research isdescriptive linguistic analysis which tries to explain the standard forms of language.The source of the results was that there were 7 intra-system shift data shifts fromthe translation of the Prambanan Temple tourism brochure.